2021
DOI: 10.1002/jmri.27684
|View full text |Cite
|
Sign up to set email alerts
|

Amide Proton Transfer‐Weighted Imaging and Multiple Models Diffusion‐Weighted Imaging Facilitates Preoperative Risk Stratification of Early‐Stage Endometrial Carcinoma

Abstract: Background Endometrial carcinoma (EC) risk stratification is generally based on histological assessment. It would be beneficial to perform risk stratification noninvasively by MRI. Purpose To investigate the application of amide proton transfer‐weighted imaging (APTWI), monoexponential, biexponential, and stretched exponential intravoxel incoherent motion (IVIM), and diffusion kurtosis imaging (DKI) for the evaluation of risk stratification in early‐stage EC. Study Type Prospective. Population Eighty patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 40 publications
5
38
4
Order By: Relevance
“…Meng et al. used the average ADC and MD based on the total tumor volume for stage I EC risk stratification assessment, and the results showed that these values decreased with the increase in risk stratification; significant differences in the ADC and MD between the low-risk and non-low-risk groups were observed ( 19 ). In the present study, the ADC and MD were lower in the non-adenocarcinoma, stage IB, high-grade, and non-low-risk groups than those in the adenocarcinoma, stage IA, non-high-grade, and low-risk groups (all p < 0.05), which was generally consistent with the above findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al. used the average ADC and MD based on the total tumor volume for stage I EC risk stratification assessment, and the results showed that these values decreased with the increase in risk stratification; significant differences in the ADC and MD between the low-risk and non-low-risk groups were observed ( 19 ). In the present study, the ADC and MD were lower in the non-adenocarcinoma, stage IB, high-grade, and non-low-risk groups than those in the adenocarcinoma, stage IA, non-high-grade, and low-risk groups (all p < 0.05), which was generally consistent with the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have briefly reported the role of these techniques in stage I EC risk stratification ( 18 , 19 ). However, these studies either explored the application of only a single imaging technique or assessed only risk stratification without evaluating the risk stratification factors.…”
Section: Introductionmentioning
confidence: 99%
“…APT values changed with cancer type [ 56 ], histology grade [ 60 ], proliferation, as well as menstrual cycle. The APT method was co-studied with other fMRI methods [ 57 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Meng et al also studied endometrial carcinoma (EC) by using APT and the other methods [ 57 ]. The authors found that the APT values were significantly less in low-risk cases compared to those of higher risk, and moreover, that the APT values, diffusion coefficient (D), and mean kurtosis (MK) were independent predictors of risk stratification.…”
Section: Applicationsmentioning
confidence: 99%
“…In this seminal report, APTw signal intensities were significantly higher for grade 3 EEA than for grade 1 EEA [ 27 ]. Recently, this imaging marker was proven valuable in estimating histological features and risk stratification in early-stage EC [ 28 ]. In 2021, Li et al first reported the feasibility of using three-dimensional (3D) APTw imaging for identifying endometrial adenocarcinoma, that its APTw values were significantly higher than that of benign uterine lesions, and also found APTw values exhibited a moderate positive correlation with Ki-67 proliferation status [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%